Identification of a Novel ACTN4 Gene Mutation Which Is Resistant to Primary Nephrotic Syndrome Therapy. (16th December 2019) - Meng, Lingzhang; Cao, Shan; Lin, Na; Zhao, Jingjie; Cai, Xulong; Liang, Yonghua; Huang, Ken; Lin, Mali; Chen, Xiajing; Li, Dongming; Wang, Junli; Yang, Lijuan; et al.
Abstract : ACTN4, a gene which codes for the protein α -actinin-4, is critical for the maintenance of the renal filtration barrier. It is well known that ACTN4 mutations can lead to kidney dysfunction, such as familial focal segmental glomerulosclerosis (FSGS), a common cause of primary nephrotic syndrome (PNS). To elucidate whether other mutations of ACTN4 exist in PNS patients, we sequenced the ACTN4 gene in biopsies collected from 155 young PNS patients (≤16 years old). The patients were classified into five groups: FSGS, minimal change nephropathy, IgA nephropathy, membranous nephropathy, and those without renal puncture. Ninety-eight healthy people served as controls. Samples were subjected to Illumina's next generation sequencing protocols using FastTarget target gene capture method. We identified 5 ACTN4 mutations which occurred only in PNS patients: c.1516G > A (p.G506S) on exon 13 identified in two PNS patients, one with minimal change nephropathy and another without renal puncture; c.1442 + 10G > A at the splice site in a minimal change nephropathy patient; c.2191-4G > A at the cleavage site, identified from two FSGS patients; and c.1649A > G (p.D550G) on exon 14 together with c.2191-4G > A at the cleavage sites, identified from two FSGS patients. Among these, c.1649A > G (p.D550G) is a novel ACTN4 mutation. Patients bearing the last two mutations exhibited resistance to clinical therapies.